Oil palm rachis gasification for synthesis gas production (2017)
The use of fossil fuels and the environmental detriment caused by the greenhouse gas emissions has encouraged the search of new energy sources as well as processes for their use. On the other hand, the energy security has become an issue of international interest due to the changing oil prices. Colombia is a tropical country that has been characterized by its high production of palm oil currently. However, the processing of the oil palm (Elaeis guineensis) in large amounts generates a great quantity of waste biomass. The oil palm rachis is a residue that has been characterized by not receiving any use as a raw material to obtain bioenergy. This one is used as source of nutrients in the crop. Consequently, the potential of this agro-industrial residue to obtain value-added products is enormous. The present work presents an opportunity to use the oil palm rachis through its gasification to obtain synthesis gas, which is considered an energy vector and a chemical platform. In order to develop this work, the physicochemical characterization of the palm rachis, syngas production in a downstream fixed bed gasifier, the technical, economic and environmental evaluation of the gasification processes were developed. Additionally, the syngas is used as a chemical platform for the production of two value-added products and the production of bioenergy after a cogeneration cycle (Texto tomado de la fuente)